Interactive Digital Flipbooks: Enhancing Engagement and Accessibility in Education for Diverse Learners in Technology in ELT Course at Universitas Negeri Medan - Indra Hartoyo; Nora Ronita Dewi; Bahagia Saragih; Eko Isdianto; Yuni Khairina (Sustainable, 2024)
Digital tools have become increasingly popular in enhancing student engagement and accessibility, particularly in the context of English Language Teaching (ELT). This study explores the effectiveness of Heyzine digital flipbooks in improving engagement and accessibility for diverse learners in the Technology in ELT course at Universitas Negeri Medan. Using a descriptive qualitative approach, data were collected through classroom observations, lecturer interviews, focus group discussions (FGDs), surveys, and questionnaires. The findings show that digital flipbooks significantly enhance student engagement, with multimedia elements like videos, animations, and quizzes catering to different learning styles. Accessibility features, such difficulties accessing content in digital flipbooks and accessibility in mind for students with different needs, were particularly beneficial for students with learning disabilities. However, technical challenges such as slow loading times and navigation difficulties were noted, alongside concerns regarding accessibility design for students with visual, auditory, and learning disabilities. Despite these issues, 75% of students reported never feeling disengaged, and 95% of students found the interactive features most engaging. The study concludes that while digital flipbooks have great potential to foster engagement and improve learning outcomes, ongoing improvements in usability and accessibility are necessary to fully support diverse learners.